Responses of spinothalamic tract cells to mechanical and thermal stimulation of skin in rats with experimental peripheral neuropathy - Paleček, Jiří; Palečková, V; Dougherty, P.M; Carlton, S.M; Willis, W.D (Journal of neurophysiology, 1992)
1. Responses of spinothalamic tract (STT) neurons to mechanical and thermal stimulation of skin were recorded under urethane and pentobarbital anesthesia in 12 control rats and in 20 rats with experimental neuropathy. Activity of the STT cells in neuropathic rats was recorded 7, 14, and 28 days after inducing the neuropathy by placing four loose ligatures on the sciatic nerve. 2. All neuropathic animals showed guarding of the injured hindpaw and a shorter withdrawal latency from a radiant heat source of the neuropathic hindpaw than that of the sham-operated paw. 3. STT neurons in neuropathic animals showed the most profound changes 7 and 14 days after the nerve ligation. When compared with STT cells in unoperated animals, approximately half of the neurons had high background activity, responses to innocuous stimuli represented a larger percentage of the total evoked activity in wide dynamic range neurons, and the occurrence and magnitude of afterdischarges to mechanical and thermal stimuli were increased. 4. The mean threshold temperatures of heat-evoked responses of the STT cells in neuropathic animals were not different than those of cells from control animals. However, in neuropathic rats, cells reacting to small heat stimuli usually already had afterdischarges. 5. The increase in the background activity of STT cells is consistent with behavioral observations of spontaneous pain in this model of experimental neuropathy. Furthermore, the afterdischarges of STT cells may parallel the prolonged paw withdrawal in response to noxious stimuli that is seen in these animals and that is evidence for hyperalgesia. However, there was no indication of a lowered threshold for thermal stimuli as might be expected if the animals have thermal allodynia. Mechanical allodynia may have resulted from a relative increase in responsiveness to innocuous mechanical stimuli. However, responses to noxious mechanical stimuli were reduced compared with control, at least at 28 days after the ligation. Peripheral and central mechanisms responsible for the changes in responses of STT cells in neuropathic animals are suggested.
Keywords: vysoká teplota; Male; Rats; inbrední kmeny potkanů; chování zvířat; kůže; tractus spinothalamicus; Peripheral Nervous System Diseases; Electrophysiology; Spinothalamic Tracts; Animals; Hot Temperature; Physical Stimulation; zvířata; nemoci periferního nervového systému; fyzikální stimulace; mužské pohlaví; Rats, Inbred Strains; neurony; Behavior, Animal; krysa rodu Rattus; Neurons; elektrofyziologie; Skin